Indian Commodity Market: Performance Evaluation and Future Opportunities for Economic Expansion" - Sonia; Tilak Raj (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The commodity market is one of the key components of every nation's financial sector. A wide range of goods including metals, crude oil, and agricultural commodities including cotton, wheat, rubber, maize, sugar, maize, and coffee, are traded on the Indian commodity market. The Indian commodities market has a long background, but it hasn't grown much because of an intermediary prohibition on commodity trade. These days, the trading volume in this new market is expanding more quickly, which will help the Indian economy flourish. The present study aimed at examining the Indian Commodity Market's steady expansion, finding investment opportunities in commodities and exploring the various methods to get exposure to commodities. It is concluded that India's economic expansion in the next twenty years will mostly be led by a diverse range of commodities, such as energy products (both traditional and alternative), several types of metals (industrial, foundational, and valuable), polymers, and agricultural items. Therefore, exchanges, regulators, and policy makers should priorities this objective to enhance agricultural livelihoods and ensure food security.